Duty to self: moral, political, and legal self-relation - Schofield, Paul (Oxford University Press, 2021)
"To say of someone that she has a duty to herself, or that she owes it to herself to do this or that, isn't likely to raise the eyebrow of the proverbial person on the street. These forms of words often find their way into everyday talk without bringing the proceedings to a pause for clarification. With these phrases, we frequently urge others to take care of themselves, or reassure ourselves about the propriety of "looking out for number one." Popular R&B and dance songs have titles like "Owe It to Yourself" and "I Owe it to Myself." The bookstore's self-help shelves display volumes such as You Owe It to Yourself: Effective Keys to a Happier Marriage and You Owe It to Yourself: Divorce and Relationships. A recent TED Talk tells us: "You owe it to yourself to experience a total solar eclipse." Columnists recommend to advice-seekers not simply that they discharge their duties to others, but that they also mind their duties to themselves. The language of self-directed duty, it seems, is not just familiar, but pervasive"--